Effect, Photoperiod and Kinetin Effect Photoperiod and Kinetin Concentration on In Vitro Progagation of Potato (Solanum tuberosum) 'Granola' as Bioplastic Raw Material - Raina Fazira; R S Handayani; Ismadi Ismadi; Nasruddin Nasruddin; Hafifah Hafifah; K Yusfie; S Hafidhah (LPPM Universitas Malikussaleh, 2024)
Potato is a horticulture plant that contains complex nutrition like high carbo and phosphor. Low potato productivity can be caused by the use of low-quality (degenerate) seed potatoes that are conventionally propagated by the farming community. Tissue culture techniques can be an effective solution to produce healthy and disease-free seed potatoes. This study aimed to examine the combination treatment between photoperiod (P) and Kinetin (K) on the growth of granola potato micro cuttings in vitro. This research was conducted at the Plant Tissue Culture Laboratory, Faculty of Agriculture, Malikussaleh University, from February to April 2022. This study used a split-plot design in a completely randomized design. The main plot was photoperiod (0 hours ligth and 24 hours light). The sub plot was concentration of kinetin (0; 2; 4 ppm). The resut showed that there was an interaction between the treatment of photoperiod and kinetin concentration on the growth of ‘Granola’ potato micro cuttings on the variables of shoot growth percentage, number of shoots, number of leaves, and number of roots. The best treatment was 24 hours of light + 4 ppm kinetin.